Memory Maps The State and Manchuria in Postwar Japan - Tamanoi, Mariko Asano (The World of East Asia, 2008)
Between 1932 and 1945, more than 320,000 Japanese emigrated to Manchuria in northeast China with the dream of becoming land-owning farmers. Following the Soviet invasion of Manchuria and Japan's surrender in August 1945, their dream turned into a nightmare. Since the late 1980s, popular Japanese conceptions have overlooked the disastrous impact of colonization and resurrected the utopian justification for creating Manchukuo, as the puppet state was known. This re-remembering, Mariko Tamanoi argues, constitutes a source of friction between China and Japan today. Memory Maps tells the compelling story of both the promise of a utopia and the tragic aftermath of its failure. An anthropologist, Tamanoi approaches her investigation of Manchuria's colonization and collapse as a complex "history of the present," which in postcolonial studies refers to the examination of popular memory of past colonial relations of power.